Forced convection boundary layer stagnation-point flow in Darcy-Forchheimer porous medium past a shrinking sheet - Abu Bakar, Shahirah; Md. Arifin, Norihan; Nazar, Roslinda; Md. Ali, Fadzilah; Pop, Ioan (Global Digital Central, 2016)
A mathematical model of forced convection boundary layer stagnation-point slip flow in Darcy-Forchheimer porous medium over a shrinking sheet is presentedin this paper. The governing partial differential equations are transformed into ordinary differential equation using self-similarity transformations which are then solved numerically with shooting method. A parametric study of the physical parameters involved in the problem is conducted and representative set of numerical results are presented through graphs and tables, and are discussed.